(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This paper explores the administrative workflows, management processes, and practical deployment of distance learning technologies through specialized information systems. Specifically, it analyzes the key functional attributes of core system modules that ensure a seamless and high-performing learning environment.